A Cultural Comparison of Personality Profiles of U.S. and Japanese Centenarians. (July 2021) - da Rosa, Grace D.; Martin, Peter; Kim, Joseph; Russell, Daniel; Abraham, W. Todd; Gondo, Yasuyuki; Hirose, Nobuyoshi; Masui, Yukie; Poon, Leonard W.
The purpose of this study was a cross-cultural examination of centenarians' personality through a person-centered approach to examine if there is a "resilient" personality profile consistent across cultures. Proxy reports information was obtained from family and close friends of 239 U.S. centenarians from the Georgia Centenarians Study and 272 Japanese centenarians from the Tokyo Centenarian Study. Latent profile analyses were conducted to identify personality profiles in centenarians from the United States and Japan. Two personality profiles were identified in both samples: a "resilient" personality profile and "nonresilient" personality profile. The "resilient" group had higher levels of positive personality traits with higher scores on agreeableness and extraversion and lower scores on neuroticism, conscientiousness, and openness. The "nonresilient" group had higher scores on neuroticism and lower scores on extraversion, openness, agreeableness, and conscientiousness. Fifty percent of U.S. centenarians and 65% of Japanese centenarians were in the "resilient" group.